Adipose Tissue-Derived Mesenchymal Stem Cells Exert In Vitro Immunomodulatory and Beta Cell Protective Functions in Streptozotocin-Induced Diabetic Mice Model - Hossein Rahavi; Seyed Mahmoud Hashemi; Masoud Soleimani; Jamal Mohammadi; Nader Tajik (Journal of Diabetes Research)
Regenerative and immunomodulatory properties of mesenchymal stem cells (MSCs) might be applied for type 1 diabetes mellitus (T1DM) treatment. Thus, we proposed in vitro assessment of adipose tissue-derived MSCs (AT-MSCs) immunomodulation on autoimmune response along with beta cell protection in streptozotocin- (STZ-) induced diabetic C57BL/6 mice model. MSCs were extracted from abdominal adipose tissue of normal mice and cultured to proliferate. Diabetic mice were prepared by administration of multiple low-doses of streptozotocin. Pancreatic islets were isolated from normal mice and splenocytes prepared from normal and diabetic mice. Proliferation, cytokine production, and insulin secretion assays were performed in coculture experiments. AT-MSCs inhibited splenocytes proliferative response to specific (islet lysate) and nonspecific (PHA) triggers in a dose-dependent manner (P<0.05). Decreased production of proinflammatory cytokines, such as IFN-γ, IL-2, and IL-17, and increased secretion of regulatory cytokines such as TGF-β, IL-4, IL-10, and IL-13 by stimulated splenocytes were also shown in response to islet lysate or PHA stimulants (P<0.05). Finally, we demonstrated that AT-MSCs could effectively sustain viability as well as insulin secretion potential of pancreatic islets in the presence of reactive splenocytes (P<0.05). In conclusion, it seems that MSCs may provide a new horizon for T1DM cell therapy and islet transplantation in the future.